Races to Modernity : Metropolitan Aspirations in Eastern Europe, 1890-1940 - Kohlrausch, Martin; Behrends, Jan C. (Book collections on Project MUSE., 2014)
"The book asks how far the model of the European City can be applied to the cities of Eastern Europe which massively expanded from the second half of the 19th century on but often lacked some of the fundamentals of the European urbanity in the Weberian sense. The authors employ a broad focus and look at metropolitan cities between Helsinki and Athens, Warsaw and Moscow. The period under investigation begins with the 1890s when East European societies entered an 'age of great acceleration' and stops with the outbreak of World War II which not only destroyed but also socially and ethnically altered many metropolitan cities of Eastern Europe. While before the First World War most of Eastern Europe was subsumed in the Habsburg, Romanov, and Ottoman empires, new (nation- ) states and socialist ideologies shaped post-1918 urban development. For the majority of the new capitals created by the post-war order the state remained the main proponent of change. Both, historical preconditions--the economic situation, the legacy of the empires--and the experience of the upheaval of 1917/18 contributed to this particularity of the region. On the other hand Western Europe and her urban experts continued to be and became even stronger points of reference. The volume discusses the peculiar relationship between state, city and the challenges of modernity in the Eastern Europe with a focus on urban planning in the wider sense of the word. In particular, the different chapters of the book ask how far--given the omnipresent, albeit often idealized example of Western metropolitan cities--a 'reflective modernization' may be identified as a common marker of cities in the region under observation"--Provided by publisher